2005
DOI: 10.5713/ajas.2005.370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus reuteri-based Direct-fed Microbial Supplementation for Growing-Finishing Pigs

Abstract: Two experiments were conducted to evaluate the effects of direct-fed microbial supplementation on the growth performance and nutrient digestibility in pigs. In experiment 1, forty eight pigs were used in a 42-d growth assay. There were four pigs per pen and three pens per treatment. Dietary treatments included 1) NC (without antibiotic basal diet), 2) PC (NC diet+0.1% antibiotic, 100 g/kg chlortetracycline), 3) DFM-1 (NC diet+0.2% Lactobacillus reuteri and Lactobacillus salivarius complex) and 4) DFM-2 (NC die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…These beneficial effects of antibiotic and probiotic supplementation on growth performance are consistent with the results of Cromwell (2001), Shon et al (2005), and Wang et al (2011). Lactobacilli bacteria are natural inhabitants of the gastrointestinal tracts of piglets.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These beneficial effects of antibiotic and probiotic supplementation on growth performance are consistent with the results of Cromwell (2001), Shon et al (2005), and Wang et al (2011). Lactobacilli bacteria are natural inhabitants of the gastrointestinal tracts of piglets.…”
Section: Discussionsupporting
confidence: 81%
“…Min et al (2004) reported the positive effects of 0.04% Bioplus 2B in the DM and N digestibilities of nursery pigs. Conversely, Shon et al (2005) and Wang et al (2009) reported no improvement in nutrient digestibility of growing pigs by dietary Lactobacillus or Bacillus-based probiotic supplementation, respectively. Improvement of apparent digestibility of nutrients by probiotics and antibioitcs could be attributed to increased nutrient availability for absorption via suppression of growth and metabolic activities of harmful gut microbiota along with simultaneous alteration of the intestinal morphology (Shim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, probiotic supplements may be more effective under stress such as practical field conditions [45, 46]. This might be one reason for the missing effect of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%